The Understanding of Special Education Teachers About The Implementation of Inclusive Education In Public Schools - Efendi, Mohammad; Yassin, Mohd Hanafi Mohd; Ummah, Ummi Syafiul; Pradipta, Risqi Fajar; Dewantara, D imas Arif (International Journal of Psychosocial Rehabilitation, 2020)
-The purpose of this study is to analyze the understanding of special education teachers in providing inclusive education services in public schools. Based on information collected from 47 special teachers in Malang City and surrounding areas, it can be concluded that teaching experience, pre-service education, in- service training contributes significantly to the understanding of Special Teachers in implementing inclusive education.